2019
DOI: 10.1057/s41292-019-00150-y
|View full text |Cite
|
Sign up to set email alerts
|

Opposition to the forensic use of DNA in France: the jurisdiction and veridiction effects

Abstract: The use of genetic databases by the police and justice system has risen dramatically over the last twenty years, particularly in France, which has the second largest database in Europe. In such a context, this article analyses the legal and scientific effects of the forensic use of DNA on the formation of individuals' (bio)identities in France. More specifically, we adopt a line of investigation that builds out from forms of resistance to genetic databases. Our methodology draws on a series of interviews and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This is important to note as some variables included in the study relate to strategies to avoid detection (e.g., destroying and removing evidence, or wearing gloves) that are associated with “forensic awareness” ( Davies, 1992 ). Although the use of DNA evidence emerged in the 1980s, it was not widely used by French Police until 1998 ( Vailly & Bouagga, 2019 ), and as a result, some concerns with capturing “forensic awareness” variables in offenses that occurred during the 1990s are warranted. This possibility is limited, however, given the fact that a large proportion of the cases (86.6%) occurred since the year 2000.…”
Section: Methodsmentioning
confidence: 99%
“…This is important to note as some variables included in the study relate to strategies to avoid detection (e.g., destroying and removing evidence, or wearing gloves) that are associated with “forensic awareness” ( Davies, 1992 ). Although the use of DNA evidence emerged in the 1980s, it was not widely used by French Police until 1998 ( Vailly & Bouagga, 2019 ), and as a result, some concerns with capturing “forensic awareness” variables in offenses that occurred during the 1990s are warranted. This possibility is limited, however, given the fact that a large proportion of the cases (86.6%) occurred since the year 2000.…”
Section: Methodsmentioning
confidence: 99%
“…28 France has the second-largest DNA database in Europe, with the Fichier National Automatisé des Empreintes Génétiques (FNAEG) established in 1998. 29 The Australian National Criminal Investigation DNA Database (NCIDD) has been in use nationally since April 2001, and since then more than 1.2 million DNA profiles have been uploaded. 30 In 2018, an investigation conducted by the South Australian Police resulted in the intelligence lead, arrest, and conviction of an individual, which is believed to be the first conviction using familial search techniques in Australia.…”
Section: International Use Of Familial and Moderate Stringency Searchesmentioning
confidence: 99%
“…Two analyses of forensic DNA database performance have found that adding crime scene samples makes a bigger contribution to aiding investigations than expanding the database by including more offenders. 29 Given that many states lack the resources to analyze crime scene DNA in a timely manner, familial DNA searching may be an inefficient use of resources better spent on conventional DNA testing. Some accounting of familial searching expenses is needed to better appreciate the costs and benefits of this forensic DNA database application.…”
Section: Cost Estimatesmentioning
confidence: 99%
“…This briefly summarized case illustrates the use of a new technique in forensic science, different from the now traditional DNA profile tests that have been used for two decades in many countries. While the aim of DNA profiling is to identify suspects by comparing their DNA profiles with, for example, a stain left at a crime scene (Vailly and Krikorian 2018;Vailly and Bouagga 2019), this new technique aims to predict a suspect's appearance oreven though this was not done in the Lyon case-their geographical origin, with a view to helping the police investigation. Certain social actors call this approach "phenotyping" or producing a "DNA composite sketch" (portrait-robot génétique in French) although this last label seems inaccurate, as we shall see, given the relatively limited number of features that can be analyzed.…”
mentioning
confidence: 99%